Internal structure of Erebus volcano, Antarctica imaged by high‐resolution active‐source seismic tomography and coda interferometry. Issue 3 (25th March 2013) - Zandomeneghi, D.; Aster, R.; Kyle, P.; Barclay, A.; Chaput, J.; Knox, H.
Abstract : [1] Erebus volcano, Antarctica has hosted a persistent convecting phonolite lava lake for over 40 years. The lake produces small (VEI 0–1) Strombolian eruptions resulting from gas slugs rising through the upper conduit system. High‐resolution (to scale lengths of several hundreds of meters) three‐dimensional P‐wave tomographic velocity images were obtained to a depth of approximately 600 m below the volcano surface. Data were collected using 91 seismographs deployed over an approximately 4 by 4 km area of the summit region. Seismic illumination was provided by 12 chemical shots emplaced in shallow snow and ice boreholes. P‐wave direct arrival travel‐time measurements were used to invert for strong velocity anomalies (with spatial variations in Vp exceeding ±1 km/s) associated with the uppermost few km. Shallow anomalies correlate with fumarolic ice caves, a prominent radial chilled dike, and ring structures associated with the caldera rim. Conduit structures feeding the lava lake and other vents within the Inner Crater are evidently too small (e.g., less than many 10 s of meters) to be imaged under the resolution limits of this experiment. However, combined velocity and coda interferometry scattering intensity images identify near‐summit regions with both low velocity and high scattering that are candidates for magma accommodation. Results indicate a nonaxisymmetric near‐summit magmatic system that is likely constrained by heterogeneous structures in the uppermost volcano. The most extensive volume of near‐summit magma likely resides approximately 500 m NW of the active Inner Crater vents at depths of 500 m and more below the surface. Key Points: Joint seismic imaging of P travel time and coda interferometry scattering Highly complex and offset magmatic system High‐resolution imaging of an active volcano